Effect of heat treatments on the microstructure and mechanical properties of a Ti–5Al–5Mo–5V–1Fe–1Cr alloy - Changchang Liu; Yanghuanzi Li; Ji Gu; Xiaotao Liu; Hao Zhang; Hongge Yan; Min Song (Journal of Materials Research and Technology)
In this work, a duplex-step rolling deformation, comprising single phase region rolling and dual phase region rolling, and three kinds of heat treatments were applied on an as-cast Ti-55511 alloy to enhance the mechanical properties. Tensile testing results show that a high tensile strength (∼1367 MPa) coupled with a decent ductility to failure (∼6.5%) can be obtained by the duplex-step heat treatment, including a high temperature heat treatment (930 °C) for a short time (3 min) followed by aging at a lower temperature (600 °C) for 120 min. Microstructure characterizations indicate that the high strength of the alloy can be attributed to the distribution of multi-scale α phase, and the good ductility of the alloy may stem from the existence of the Widmanstätten structure near the grain boundaries, which alleviates the strain localization between the grain boundary and the grain interior.